Osteoporosis - A childhood illness? - Stránský, Miroslav (Auctores Publishing LLC, 2019)
Osteoporosis is a multifactor illness of the bone mass, the risk of which can be decreased by adequate nutrition and lifestyle. The prevention must start in childhood, because in the period, the bone mass information is very intense, and reaching the peak bone mass is necessary basis for the ideal bone density at older age.
Keywords: osteoporosis; metabolism; risk factors; nutrition; prevention